Penerapan Motivasi sebagai Faktor Penting dalam Meningkatkan Kinerja Sumber Daya Manusia di SPBU Darussalam Grup - Sulaeman, Eman; Ramadhan, Muhammad Rizki; Khoerunnisa, Najwa; Novelia, Riani Rahma; Sasmita, Tegar Permata (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Providing motivation to employees is very necessary in a company, because with motivation from the leadership of the company, employees automatically feel valued for what they do, automatically the performance of human resources increases, so that friendship and good relations are maintained between company leaders and their employees. . This study aims to determine the application of motivation as an important factor in improving human resource performance at the Darussalam Group gas station. The type of research used was descriptive qualitative, namely a symptom and fact of the object at the time the research took place. This research was carried out at the Darussalam Group gas station by selecting 1 informant who was considered representative of each employee, namely 1 field supervisor as a key informant. Data collection techniques used in this study were interviews, observation and documentation. The results of the research show that work motivation is very important for employees to support their performance. And the performance of the Darussalam Group Gas Station employees can be said to be good which can be seen from the creation of a job satisfaction for employees and can improve the company's image. Keywords: motivation, human resources.